UKRAINIAN RADIO METEOR NETWORK — DEVELOPMENT AND FIRST RESULTS - Kulichenko, M. O.; Kalyuzhnyi, M. P.; Bushuev, F. I.; Shulga, O. V.; Malynovskyi, Ye. V.; Savchuk, S. G.; Yankiv-Vitkovska, L. M.; Hrudynin, V. O. (Одеські астрономічні публікації, 2020)
The network of the meteor observation in the radio range consisting of 6 stations located in Mykolaiv (3 stations), Rivne, Lviv and Hlukhiv has been created. The main goal of the network is to expand information about meteor phenomena, including the assessment of the kinematic parameters (velocities, radiants and orbital elements) of meteoroids and their relationship with other small bodies of the Solar system (potentially hazardous asteroids approaching the Earth). The operation of the meteor observing hardware and software complex is based on the continuous receving of signals from FM radio station reflected from ionized meteor trains that occur in the Earth’s atmosphere at altitudes of 80-100 km. SDR technology is used to receive radio signals from over-the-horizon FM broadcast stations reflected by a meteor train, which has allowed to improve the sensitivity and frequency selectivity of radio signals. In 2017–2020 the network registered 1093015 meteors. The observational data are posted on the RMOB website. Diurnal variation of meteor counts and comparison with Perseids meteor stream activity are presented in the work.